All for one and one for all? Leadership approaches in complementary schools. (January 2023) - Arthur, Linet; Souza, Ana
This article explores the nature of leadership in Brazilian complementary schools in the UK. Such schools are typically parent-driven, voluntary and financially vulnerable. Using data from a questionnaire survey ( n =14; more than three-quarters of Brazilian complementary schools) and three in-depth case studies, leadership is examined in relation to five established approaches: directive, instructional, transformational, distributed and collaborative. The study found that the size of the school and the personality of the leader appeared to influence the type of leadership adopted. In terms of effectiveness, a combination of instructional leadership with an approach that motivated staff and volunteers (whether directive, collaborative or transformational, depending on the school's circumstances) seemed most appropriate to the context of complementary schools. The research illustrates the complexity of school leadership and the overlap between different models. Leadership flexibility was important in responding to the needs of staff, students and parents. The findings are transferable to mainstream schools with contexts similar to those of complementary schools, particularly small primary schools and free schools.